Analysis of the Outcomes of Combined Cross-Linking with Intracorneal Ring Segment Implantation for the Treatment of Pediatric Keratoconus. (1st February 2019) - Iqbal, Mohammed; Elmassry, Ahmed; Tawfik, Ahmed; Abou Samra, Waleed; Elgharieb, Mervat; Elzembely, Hosam; Soliman, Ashraf; Saad, Hisham; El Saman, Islam; Saeed, Ahmed; Farouk, Mahmoud; Tawfik, Tarek; et al.
ABSTRACT: Purpose : To analyze the visual and refractive outcomes of combined accelerated cross-linking with femtosecond laser intracorneal ring segment implantation for the treatment of pediatric keratoconus. Materials and Methods : This retrospective multicenter noncomparative clinical study included 63 eyes of 37 patients (age, 9–17 years) who underwent between August and September 2016 combined cross-linking with intracorneal ring segment implantation for keratoconus. Preoperative and postoperative (6, 12, and 18 months) uncorrected distance visual acuity (UDVA) and corrected distance visual acuity (CDVA), subjective refractions, keratometry (K), and pachymetry measurements were compared. Results : The postoperative spherical equivalent refraction was within ±1 D, ±2 D, and ±3 D in 19 (30.2%), 27 (42.9%), and 37 (58.8%) eyes, respectively. Only 27 eyes achieved the attempted preoperative spherical equivalent refraction. The mean spherical equivalent refraction significantly improved from −6.01 ± 2.97 to −3.13 ± 2.78 D postoperatively ( P < 0.0001). The mean K average reading significantly decreased from 48.75 ± 4.25 to 46.65 ± 3.89 D postoperatively (P < 0.0001). The mean postoperative myopic, astigmatic, and spherical equivalent corrections were −2.17 ± 2.19, −1.52 ± 2.03, and −2.93 ± 2.35 D, respectively. The mean UDVA and CDVA showed significant improvements (0.89 ± 0.33 to 0.40 ± 0.28, P < 0.0001; 0.35 ± 0.31 to 0.25 ± 0.24, P = 0.004; respectively) at 18 months postoperatively. Keratoconus progression, segment migration, and segment extrusion were seen in four (6.4%), one (1.6%), and three (4.7%) eyes, respectively, probably contributing to the lower mean postoperative CDVA. Conclusion : Cross-linking plus is only partially effective for pediatric keratoconus. Despite some improvements in vision and keratometry measures, it resulted in complications such as keratoconus progression, segment extrusion, and segment migration that affected the vision in some patients. These findings suggest an assessment of standard epithelium-off collagen cross-linking as a sole procedure to treat pediatric keratoconus in future studies.